A Confirmatory Factor Analysis of Teaching Presence Within Online Professional Development - Miller, Melinda G.; Hahs-Vaughn, Debbie L.; Zygouris-Coe, Vicky (Online Learning, 2014)
The Community of Inquiry model provides a framework for recognizing and evaluating interpersonal behaviors in online educational settings. One of its three components, teaching presence, describes behaviors that are under the auspices of the online instructor. By examining behaviors through the theoretical lens provided by teaching presence, and by measuring them with the Teaching Presence Scale (TPS), it may be possible to better understand the most effectively online instruction practices. The purpose of the study was to confirm the factor composition of TPS in an online professional development course and to determine the relationship between teaching presence and student satisfaction. Participants (n = 718) were in-service educators enrolled in online professional development. Confirmatory factor analysis results provided strongest support for a three-factor TPA model using 17 of the 28 original TPS items and evidence of a strong relationship between TPS and student satisfaction. The implications for practice center primarily on how enhanced knowledge of teaching presence may be used to develop instructor/facilitators as online educators of adults. It is important that such instructors have a solid knowledge base in their field, as well as knowledge and experience with andragogy.